Identification of molecular crystals capable of undergoing an acyl-transfer reaction based on intermolecular interactions in the crystal lattice - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Chemistry-A European Journal, 2013)
Investigation of the intermolecular acyl-transfer reactivity in molecular crystals of myo-inositol orthoester derivatives and its correlation with crystal structures enabled us to identify the essential parameters to support efficient acyl-transfer reactions in crystals: 1)the favorable geometry of the nucleophile (OH) and the electrophile (CO) and 2)the molecular assembly, reinforced by CH interactions, which supports a domino-type reaction in crystals. These parameters were used to identify another reactive crystal through a data-mining study of the Cambridge Structural Database. A 2:1 co-crystal of 2,3-naphthalene diol and its di-p-methylbenzoate was selected as a potentially reactive crystal and its reactivity was tested by heating the co-crystals in the presence of solid sodium carbonate. A facile intermolecular p-toluoyl group transfer was observed as predicted. The successful identification of reactive crystals opens up a new method for the detection of molecular crystals capable of exhibiting acyl-transfer reactivity.
Keywords: Acylation; domino reactions; intermolecular interactions; solid-state reactions; X-ray diffraction

Acyl-transfer reactions in molecular crystals: reactivity correlation with crystal structure - Gonnade, Rajesh G.; Shashidhar, Mysore S. (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: crystal engineering; intermolecular interactions; solid-state reactions

Construction of two-component chemically reactive supramolecular assemblies-acyl migration reactions in cocrystals of napthalene-2,3-diol and its diesters - Bahadur, Vir; Gonnade, Rajesh G.; Tamboli, I. Majid; Krishnaswamy, Shobhana; Shashidhar, Mysore S. (ChemPlusChem, 2021)
Reactions in solids are of contemporary interest due to applications in pharmaceutical industries to environmental sustainability. Although several reactive crystals that support chemical reactions have been identified and characterized, the same cannot be said about reactive cocrystals. Earlier we correlated the facile acyl group transfer reactions in crystals with supramolecular parameters obtained from the crystal structures. The structure-reactivity correlation revealed the requirement of proper juxtaposition of electrophile (C=O) and the nucleophile (OH) with distance (similar to 3.2 angstrom) and angle (similar to 90 degrees) along the chain structure. The current article describes the preparation of cocrystals that are capable of supporting intermolecular acyl group transfer reactions in a group of structurally similar molecules. The cocrystals of naphthalene 2,3-diol and its corresponding diesters showed a facile solid state acyl transfer reaction, which has been well correlated with their crystal structures.
Keywords: Acylation; domino reactions; intermolecular interactions; reaction in cocrystal; solid-state reactions; X-ray diffraction